A produção da (In)visibilidade da pessoa protadora de deficiência mental: cartografia de uma comunidade Batista - Esperandio, Mary Rute Gomes (2001)
The invisibility of people with mental disability is linked to the interweaving of several strands of the social web, including economic, political, cultural, religious, psychological, and sociological elements. Formal religion, therefore, represents one of these threads that acts upon the processes resulting in the exclusion/inclusion of the mentally disable person. Thus, the present study presents an investigation into how these processes that produce invisibility are composed, within theological discourse, in social spheres, and with the participation of formal religion. The choice of methodology applied cartography is intended to trace which elements in the day-to-day life of a Baptist Community can function as transforming elements that affirm life, in its multiplicity and its singularity. The ethical choice that transverses and defines this investigation is clear: the intention is to sustain life in its processes of expansion.